POLICY BRIEF Konseling Perubahan Perilaku bagi Pelaku Kekerasan dalam Rumah Tangga dalam Sistem Peradilan Pidana - Saeroni; Triantono (Fakultas Syariah - IAI Al-Qolam Malang, 2021)
This policy brief was prepared based on the results of research conducted on “Pyco-legal Aspects in Taking Action against Perpetrators of Domestic Violence in DI. Yogyakarta.